ХІРУРГІЯ ВНУТРІШНЬОШЛУНОЧКОВИХ ПУХЛИН. ЕНДОСКОПІЧНІ МОЖЛИВОСТІ - Паламар, О.І.; Гук, А.П.; Тесленко, Д.С.; Оконський, Д.І.; Аксьонов, Р.В. (Українські медичні вісті, 2023)
ХІРУРГІЯ ВНУТРІШНЬОШЛУНОЧКОВИХ ПУХЛИН. ЕНДОСКОПІЧНІ МОЖЛИВОСТІ